(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study explores how economic expansion and environmental sustainability interact in Malaysia, focusing on their non linear relationship through the Multiple Threshold Nonlinear Autoregressive Distributed Lag (MTNARDL) model. By accounting for asymmetries and structural thresholds, the analysis captures dynamics that are often missed by conventional models. The findings suggest that while moderate economic growth is accompanied with lower carbon emissions, the benefits taper off and reverse beyond certain growth levels, where further expansion contributes to environmental deterioration. Additional analysis shows that low to moderate population growth supports emission control, but higher rates exert negative pressure. Energy consumption consistently raises emissions, although its marginal impact declines at higher usage thresholds. These results point to the need for differentiated policy responses that consider threshold effects. For Malaysia to achieve sustainable development, economic, demographic, and energy policies must be aligned to manage trade-offs effectively.